1994
DOI: 10.1007/bf00347504
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental stressors on blood-glucose levels in sea hares, Aplysia dactylomela

Abstract: Abstract. Effects of natural stressors such as tidepool strandings, air exposure, and low salinity on blood-glucose levels were investigated in the sea hare Aplysia dactylomela from shallow areas of Discovery Bay, Jamaica. All treatments produced large and significant elevations in blood-glucose titre, 1.5-to 2.3-fold above baseline levels of 25 to 35 gg glucose ml-1. Response times were variable, with significant elevations being manifested within 30 to 120 min from initiation of the stressor. Recovery was sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Glucose levels in the haemolymph of H. laevigata rise after exercise stress and in response to increasing temperature [43]. This is consistent with findings on the heterobranch molluscs Aplysia dactylomela [44,45] and A. californica [46]. Haldane [43] found no concurrent drop in the glycogen levels during exercise stress, suggesting that this activity is supported by aerobic metabolism, in contrast to Baldwin et al [47], who reported reduced glycogen levels after exercise in H. iris, and that anaerobic glycolysis in H. iris also results in the production of lactate and a concomitant fall in the pH.…”
Section: In Vitro Biochemical Tests Of Stress In Abalonesupporting
confidence: 86%
“…Glucose levels in the haemolymph of H. laevigata rise after exercise stress and in response to increasing temperature [43]. This is consistent with findings on the heterobranch molluscs Aplysia dactylomela [44,45] and A. californica [46]. Haldane [43] found no concurrent drop in the glycogen levels during exercise stress, suggesting that this activity is supported by aerobic metabolism, in contrast to Baldwin et al [47], who reported reduced glycogen levels after exercise in H. iris, and that anaerobic glycolysis in H. iris also results in the production of lactate and a concomitant fall in the pH.…”
Section: In Vitro Biochemical Tests Of Stress In Abalonesupporting
confidence: 86%
“…In fish, a similar blood glucose response is observed due to acute stress caused by transport, handling, netting and confinement (Kubįay and Uluköy 2002), lice infestation (Mustafa et al 2000) and elevated temperatures . Glucose in crustaceans can be elevated in response to heavy metals (Lorenzon et al 2000) and in sea hares due to atmospheric exposure (Carefoot 1994). Similarly, when subjected to freezing stress worm extracts display elevated glucose levels, the levels of which varied according to species and freeze-tolerance (Bundy et al 2003).…”
Section: Discussionmentioning
confidence: 98%
“…In aquatic animals facing stress, glycogen degradation and glucose uptake can be accelerated to provide more energy for damaged cells (Lin et al, 2018). Several studies have shown that glucose levels can be used to assess stress responses in mollusks, including abalone (Carefoot, 1994; Haldane, 2002; Hooper et al, 2007). As elevated hemolymph glucose levels are a common stress response in marine invertebrates, metabolic markers including plasma glucose can generally be used to assess stress status in abalone (Chen et al, 2023).…”
Section: Discussionmentioning
confidence: 99%